A self-powered analog sensor-data-logging device based on Fowler-Nordheim dynamical systems - Darshit Mehta (Nature Portfolio, 2020)
Designing ultra-low-power sensing and data-logging techniques with battery-free operation of sensor nodes remains a challenge. Here, the authors present a self-powered sensor-data-logger device that records a cumulative measure of the sensor signal intensity over its entire duration.